Prognostic value of amplitude‐integrated EEG in neonates with high risk of neurological sequelae. Issue 2 (7th February 2020) - Yuan, Xiao; Kang, Wenqing; Song, Juan; Guo, Jing; Guo, Lanlan; Zhang, Ruili; Liu, Shasha; Zhang, Yaodong; Liu, Dapeng; Wang, Yong; Ding, Xue; Dong, Huimin; et al.
Abstract: Objective: To determine the efficacy and the prognostic value of amplitude‐integrated electroencephalography (aEEG) in term and near‐term neonates with high risk of neurological sequelae. Methods: Infants of ≥35 weeks of gestation diagnosed with neonatal encephalopathy or with high risk of brain injury were included. All eligible infants underwent aEEG within 6 h after clinical assessment. The infants were followed up 12 months to evaluate neurological development. Results: A total of 250 infants were eligible, of which 85 had normal aEEG, 81 had mildly abnormal aEEG, and 84 had severely abnormal aEEG. Of these infants, 168 were diagnosed with different neonatal encephalopathies, 27 with congenital or metabolic diseases, and 55 with high risk of brain injury. In all, 22 infants died, 19 were lost to follow‐up, and 209 completed the follow‐up at 12 months, of which 62 were diagnosed with a neurological disability. Statistical analysis showed that severely abnormal aEEG predicted adverse neurological outcome with a sensitivity of 70.2%, a specificity of 87.1%, a positive predictive value of 75.6%, and a negative predictive value of 83.7%. Interpretation: aEEG can predict adverse outcomes in high‐risk neonates and is a useful method for monitoring neonates with high risk of adverse neurological outcomes.